A ‘normal’ life: a qualitative study exploring parents’ experiences of everyday life with a child diagnosed with atopic dermatitis and atopic comorbidities - Gitte Færk; Elisabeth Søndergaard; Lone Skov; Kirsten Skamstrup Hansen; Susanne Reventlow (Scandinavian Journal of Primary Health Care)
Introduction Atopic dermatitis (AD) and related atopic diseases are among the chronic health conditions that are becoming more common in children. Children with AD may develop atopic comorbidities, which makes it more difficult to manage treatment and necessitates more precautions in the child’s everyday life. The parents of chronically ill children play a key role as the children’s primary carers. This article explores the experiences of parents with the everyday tasks related to their children’s illnesses.Methods Face-to-face interviews in the Capital Region of Denmark, with eleven families with children, aged between one and five years, with AD and at least one atopic comorbidity (food allergy, allergic rhinoconjunctivitis or asthma),Results We argue that, aside from the immediate tasks directly linked to the child’s treatments, there are numerous other types of tasks, both inside and outside the home, that emerge when a family adjusts to living with a child with AD and atopic comorbidities. We present three major strategies that parents use to protect their child: risk avoidance, pursuing a normal childhood, and good parenting. These strategies are closely related to the parents’ wish to give their child as normal a childhood as possible.Conclusion Based on the findings, we suggest that healthcare professionals, beside the medical examination and treatment, are sensitive and attentive towards the large amounts of invisible work that parents of children with AD and atopic comorbidities accomplish and maintain awareness that parents may downplay the workload. Knowing the patients as persons can help facilitate and strength a trusting relationship.